Investigation of the Effects of Incorrect Installation of Air Conditioning Systems on Electricity Consumption Cost - Ergen, Ruveyda; Gürtürk, Mert (My University, 2023)
Changes in air temperatures with the effect of global warming are seen with increasing temperatures especially in summer months. Due to temperature increases, the use of air conditioners is increasing in order to provide the desired comfort conditions. As a result of the researches, it was determined that the air inlets were closed as a result of incorrect installation or use of the condenser unit of the air conditioning systems and the electricity consumption increased because the desired amount of air passage could not be achieved. Within the scope of this study, the authors examined the cost of electricity consumed by the air conditioning system in case of incorrect installation or use for 12 different countries. As a result of the analysis made for Turkey, the cost of electricity consumption as a result of incorrect installation practices of the air conditioning system caused an annual cost of approximately 56-62.78 $ more than the electricity consumption cost of the reference system.
Keywords: Electricity Consumption; Global Warming; Air Conditioning Systems; Incorrect Installation.